2019
DOI: 10.1111/jam.14399
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a bioluminescent bioreporter from an environmentally sourced mercury‐resistantEnterobacter cloacaestrain for the detection of bioavailable mercury

Abstract: Aim Escherichia coli is the conventional choice as the host strain for whole‐cell bioreporter construction due to its well‐understood genetics and well‐established cloning protocols. However, for real‐world environmental biosensing applications, it is often beneficial to use a bacterial strain derived directly from the environment under study to better ensure chemical target specificity and optimal response time. The aim of this study was to develop a whole‐cell bioreporter for detection of bioavailable mercur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This is because the sensitivity and response of individual strains vary under the stress of different contaminants (Phyo et al, 2021). For example, for the construction of WCB to detect mercury, Din et al (2019) isolated mercury-resistant bacteria, an Enterobacter cloacae strain, from a contaminated soil environment. They reported that their bioreporter was both more sensitive and faster than other bireporters constructed with model E. coli bacterial strains.…”
Section: Host Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the sensitivity and response of individual strains vary under the stress of different contaminants (Phyo et al, 2021). For example, for the construction of WCB to detect mercury, Din et al (2019) isolated mercury-resistant bacteria, an Enterobacter cloacae strain, from a contaminated soil environment. They reported that their bioreporter was both more sensitive and faster than other bireporters constructed with model E. coli bacterial strains.…”
Section: Host Strainmentioning
confidence: 99%
“…Chemical instrumental methods are used to analyze the total concentrations of pollutants (Kolpin et al, 2002). However, the total concentration of a contaminant is not always related to its toxicity, it has been demonstrated that bioavailability is a prerequisite for toxicity (Wells et al, 2005a;Fairbrother et al, 2007;Din et al, 2019). In other words, the chemical analysis data are inadequate to efficiently reflect the biological impacts of toxic substances (Axelrod et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…15 In previous studies, only luciferase-based whole-cell biosensors could respond to Hg(II) in the nanomolar range. 38,39 Due to the signal amplication effect, the LOD of a pigment-based biosensor is comparable to a biosensor employing enzymatic reporters, including b-galactosidase and luciferase. However, its advantage over these traditional biosensors is its independence from expensive substrates and instruments.…”
Section: The Metabolically Engineered Biosensor In Response To Bioava...mentioning
confidence: 99%
“…However, the biosensor sensitivity is usually determined by genetic circuit engineering and types of reporter genes ( Gupta et al, 2019 ; Hui et al, 2020 ). Metalloregulator MerR is a Hg(II)-responsive transcriptional factor, which has been employed to develop bacterial whole-cell biosensors using luciferase ( Din et al, 2019 ), β-galactosidase ( Hansen and Sorensen, 2000 ), fluorescence protein ( Zhang et al, 2021 ), and visual pigments ( Guo et al, 2021a ; Hui et al, 2021a ) as the signal outputs. All of these above bacterial biosensors responded to Hg(II) with high selectivity and variable sensitivity.…”
Section: Introductionmentioning
confidence: 99%